Management of Long-Term Sores and Ulcers of Breast Cancer Survivors With Chinese Herbal Medicines: A Case Report - Zhang, Yuanfeng; Zhang, Bing; Zhou, Weilong; Lu, Tao (Frontiers in Psychiatry, 2022)
Background: The treatment of long-term sore and ulcer of breast cancer metastatic recurrence is a serious challenge with rare successful cases being documented. Herein we reported a successful case from Internal Vitality Supporting Method of Chinese herbal medicines(CHM). Case summary: A 54-year-old Chinese female patient, 10 years after breast cancer surgery, developed metastatic lesions in the lung. Thereafter she received radiofrequency ablation and adjuvant treatments for 1 year with severe sequelae, left unhealed sore and ulcer. She became frustrated and depressive. And subsequently sought exclusive Traditional Chinese medicine (TCM) treatment under the guidance of a traditional Chinese medicine physician. The patient's condition was categorized as Qi (or vitality) deficiency related sore and ulcer. Up to now, the patient still follows a traditional Chinese medicine therapeutic regimen based on the Internal Vitality Supporting Method of Chinese herbs. Conclusion: The sore and ulcer from surgical wound was healed. Over the past 6 months, her tumor markers (CEA) has remained stable. There is need for psychosocial support after acute treatment and in the long-term for the cancer survivors.